LOCAL-SCALE CLIMATE VARIABILITY AND TRENDS IN A VULNERABLE RURAL LANDSCAPE, NORTHWEST ETHIOPIA - Likinaw, Aimro; Alemayehu, Arragaw; Bewket, Woldeamlak (Malaysian Journal of Tropical Geography (MJTG), 2022)
This study analyses local-scale climate variability and trends in northwest Ethiopia, covering three food-insecure and vulnerable districts, namely Lay Gaynt, Tach Gaynt, and Simada. We examined temperature and rainfall data on 4 × 4 km grids. The coefficient of variation and standardized anomaly index were used to assess the variability of rainfall and temperature. As a result, annual and seasonal rainfall show high inter-annual variability, except for the major rainy season (Kiremt), which shows a moderate coefficient of variation. The proportion of negative anomalies ranges from 39% (Lay Gayint) to 65% (Simada) over the observation period. Moreover, trend analysis was conducted using the Mann-Kendall (MK) and Innovative Trend Analysis (ITA) tests. The MK test for annual rainfall exhibited a significant rising trend for the Lay Gayint and Tach Gayint districts. The ITA for annual and seasonal rainfall indicated positive trends for Lay Gayint and Tach Gayint, while negative trends were observed in Simada. The ITA and MK tests showed similar increasing tendencies in seasonal and annual temperatures. The MK technique revealed positive patterns in 28 time series and negative patterns in 20 time series for monthly, seasonal, and annual rainfall data, whereas the ITA method revealed positive trends in 23 time series and negative trends in 25 time series. The results of this study are useful for local development planning that should take into account current and possible future climate patterns.